School Dropouts and How to Develop Them at High School Level in South Labuhan Batu Regency - Harahap, Aziddin; Gulo, Nur'ainun; Pardamean Nasution, Muda; Syahputra Harahap, Hasmi; Harahap, Arman (International Journal of Educational Research & Social Sciences, 2025)
Dropping out of school is not one of the never-ending educational problems. This problem has taken root and is difficult to solve the cause, not only because of economic conditions, but also because of chaos in the family, and others. This is also experienced by several children in South Labuhanbatu Regency. Therefore, the author wants to know and research further about the causes of children dropping out of school. This discussion is entitled "Children Dropping Out of School and How to Foster Them in South Labuhanbatu Regency". The problem in this study is what causes children to drop out of school in South Labuhanbatu Regency. How do parents and the community deal with the occurrence of children dropping out of school and how to foster them. The purpose of this discussion is to find answers to the problems above, namely to find out how many children drop out of school in South Labuhanbatu Regency, what factors cause children to drop out of school, parental attitudes, and how to foster children who drop out of school. The methods used in this study are field and library methods. The field method is carried out with three data collection techniques, namely observation, questionnaires and interviews. The results of the study showed that there were several factors causing children to drop out of school in South Labuhanbatu Regency. In general, the main problem is the family's economic condition that is not supportive. Another part is family factors that cause children in South Labuhanbatu Regency to drop out of school. There are two ways for parents and the community to deal with children who drop out of school, namely prevention efforts and coaching efforts. Prevention efforts are carried out before dropping out of school by observing, paying attention to children's problems and by making parents aware of the importance of education in order to guarantee the child's future and providing motivation to learn to the child. The coaching efforts carried out are by teaching religious and social values ​​to children, and providing work that is in accordance with their abilities so that children are busy and can avoid deviant thoughts.